Development and Characterization of Nanostructured Ni–ScSZ Composite Anodes for Solid Oxide Fuel Cells - Adaikhan, S.; Bekmyrza, K.Zh.; Baratova, A.A.; Kabyshev, A.M.; Rajagopal, P.; Aidarbekov, N.K.; Kuterbekov, K.K.; Kubenova, M.M.; Kuanysh, M.D. (Bulletin of the Karaganda University. “Physics” Series, 2025)
A thorough investigation was carried out on nickel-based anode composites with scandia-stabilized zirconia (Ni/ScSZ), fabricated using ceramic processing techniques from powders with varying particle sizes. The study emphasizes the role of initial component morphology and their ratios on sintering behavior, electrical conductivity, and polarization resistance under solid oxide fuel cell (SOFC) operating conditions. Samples incorporating nano-, submicron-, and micron-sized particles were comparatively analyzed to determine the most favorable parameters for constructing a percolative conductive network and reducing polarization losses. Experimental data obtained through dilatometry, electrical measurements, and electrochemical impedance spectroscopy confirmed that the use of nanoscale constituents leads to the formation of a dense and uniform microstructure with well-distributed porosity. Such features enhance both thermal stability and electrochemical performance. The findings highlight the potential of Ni/ScSZ-based materials as a viable alternative to conventional Ni/YSZ anodes, owing to their improved ionic conductivity and enhanced resistance to degradation, thus contributing to the advancement of more durable and efficient SOFC technologies.
Қатты оксидты отын элементтері үшін Ni–ScSZ наноқұрылымды композиттің анодтарын əзірлеу жəне сипаттау
Разработка и характеристика наноструктурированных композитных анодов Ni-ScSZ для твердооксидных топливных элементов
Keywords: solid oxide fuel cell (SOFC); Ni/ScSZ composite anode; nanopowder dispersion; polarization resistance; triple-phase boundary; electrical conductivity; sintering kinetics; activation energy; impedance spectroscopy; fabrication method